Estimated Prestroke Peak VO2 Is Related to Circulating IGF-1 Levels During Acute Stroke. (January 2017) - Mattlage, Anna E.; Rippee, Michael A.; Abraham, Michael G.; Sandt, Janice; Billinger, Sandra A.
Background . Insulin-like growth factor-1 (IGF-1) is neuroprotective after stroke and is regulated by insulin-like binding protein-3 (IGFBP-3). In healthy individuals, exercise and improved aerobic fitness (peak oxygen uptake; peak VO2 ) increases IGF-1 in circulation. Understanding the relationship between estimated prestroke aerobic fitness and IGF-1 and IGFBP-3 after stroke may provide insight into the benefits of exercise and aerobic fitness on stroke recovery. Objective . The purpose of this study was to determine the relationship of IGF-1 and IGFBP-3 to estimated prestroke peak VO2 in individuals with acute stroke. We hypothesized that (1) estimated prestroke peak VO2 would be related to IGF-1 and IGFBP-3 and (2) individuals with higher than median IGF-1 levels will have higher estimated prestroke peak VO2 compared to those with lower than median levels. Methods . Fifteen individuals with acute stroke had blood sampled within 72 hours of hospital admission. Prestroke peak VO2 was estimated using a nonexercise prediction equation. IGF-1 and IGFBP-3 levels were quantified using enzyme-linked immunoassay. Results . Estimated prestroke peak VO2 was significantly related to circulating IGF-1 levels ( r = .60; P = .02) but not IGFBP-3. Individuals with higher than median IGF-1 (117.9 ng/mL) had significantly better estimated aerobic fitness (32.4 ± 6.9 mL kg −1 min −1 ) than those with lower than median IGF-1 (20.7 ± 7.8 mL kg −1 min −1 ; P = .03). Conclusions . Improving aerobic fitness prior to stroke may be beneficial by increasing baseline IGF-1 levels. These results set the groundwork for future clinical trials to determine whether high IGF-1 and aerobic fitness are beneficial to stroke recovery by providing neuroprotection and improving function.